Konseling Kelompok Dalam Menurunkan Tingkat Kejenuhan Belajar Siswa - Ashari; Iip Istirahayu; Slamat Fitriyadi (ILIN Institute, 2021)
This study aims to know the level of learning boredom students and carrying out group counseling in reducing the learning boredom of students. This research used was pre-experimental research with one group pre-test post-test design with descriptive method. The sample of this study was 20 students, while the data collection tool used was a questionnaire. The results from the data collection tool are calculated based on the percentage and N-Gain. The results of the study illustrate that the learning boredom of students are categorized as High with a percentage of 40%, 1 person is categorized as Moderate with a percentage of 5%, 11 people are categorized as low with a percentage of 55% of their learning boredom level. Then, implementation of group counseling in reducing learning boredom of student was calculating N-Gain as much as 0.32 (G-Medium) in the medium category.